Alpenkonvention: Verkehrsprotokoll und dessen Umsetzung. - Borkenstein, Heinz-Jörg (Deutscher Verkehrs-Verl., 2008)
In den Alpen, einem Lebens-, Wirtschafts-, Verkehrs- und Erholungsraum in Europa, mit unterschiedlichsten Nutzungsansprüchen, nehmen das Güterverkehrswachstum mit einer durchschnittlich jährlichen Wachstumsrate von etwa 4 %, seine Auswirkungen auf Mensch und Umwelt sowie Maßnahmen zu seiner Bewältigung wie weitere Verlagerung des Gütertransports auf die Schiene, Lkw-Maut, Nachtfahrverbote einen breiten Raum in der öffentlichen Diskussion ein. difu

The Transport Protocol of the 1995 Alpine Convention (for the protection of the Alps) became effective, under international law, from the end of 2002. It embodies regulations for transport across the Alpine region. The main targets of this Protocol are "Sustainable transport" renunciation of building new first class trunk roads, and a shift of freight transport from road to rail. After a nation's ratification of this Protocol, the obligations thus entered into cover the three main factors of conceptualization and planning, technical measures, and monitoring. Being a part of international law, the Transport Protocol has an impact on the decisions taken by governments, administrative bodies and courts of law on a national level. The Transport Protocol seeks to contribute effectively to a sensible balance between ecology- and economy-related matters, in order to facilitate unhindered freight and passenger transport across the Alps and the Alpine region, without any adverse impact on the environment. difu
Keywords: Verkehr; Verkehrspolitik; Verkehrsplanung; Verkehrsbelastung; Güterverkehr; Güterfernverkehr; Umweltschutz; Umweltschutzrecht; Naturschutz; Erholungsraum; Alpenkonvention; Völkerrecht; Grenzüberschreitender Verkehr; Transitverkehr; Verkehrsverlagerung